The program to institutionalize meritocracy and excellence in human resource management in the Bangsamoro autonomous region in Muslim Mindanao - Salipada, Tahir; Sam, Radzak A.; Abdula, Sajid P.; Salipada, Julmaherria M.; Bayog, Maricor G.; Sam, Solayha A.; Abdula, Datuali P. (Edelweiss Applied Science and Technology, 2024)
The Civil Service Commission implemented the Program to Institutionalize Meritocracy and Excellence in Human Resource Management to enhance the performance levels of government agencies throughout the Philippines. This study aimed to examine and analyze the program’s implementation, focusing on the local government units of Parang, Maguindanao del Norte, and Datu Abdullah Sangki, Maguindanao del Sur, both within the Bangsamoro Autonomous Region in Muslim Mindanao. Utilizing a qualitative approach, the study focused specifically on the implementation of the four-core human resource management systems: recruitment, selection, and placement; learning and development; performance management; and the challenges encountered during the program’s execution. The findings revealed that the municipalities of Parang and Datu Abdullah Sangki had achieved human resource management system maturity level 2, indicating that the program was effectively implemented. While challenges were encountered during the implementation, they provided a valuable impetus for developing an organizational development intervention specifically tailored to address the needs of these local government units.